Cost-effectiveness of home versus hospital management of children at onset of type 1 diabetes: the DECIDE randomised controlled trial. Issue 5 (19th May 2021) - McCarroll, Zoe; Townson, Julia; Pickles, Timothy; Gregory, John W; Playle, Rebecca; Robling, Michael; Hughes, Dyfrig A
Abstract : Objective: The aim of this economic evaluation was to assess whether home management could represent a cost-effective strategy in the patient pathway of type 1 diabetes (T1D). This is based on the Delivering Early Care In Diabetes Evaluation trial (ISRCTN78114042 ), which compared home versus hospital management from diagnosis in childhood diabetes and found no statistically significant difference in glycaemic control at 24 months. Design: Cost-effectiveness analysis alongside a randomised controlled trial. Setting: Eight paediatric diabetes centres in England, Wales and Northern Ireland. Participants: 203 clinically well children aged under 17 years, with newly diagnosed T1D and their carers. Outcome measures: The base-case analysis adopted n National Health Service (NHS) perspective. A scenario analysis assessed costs from a broader societal perspective. The incremental cost-effectiveness ratio (ICER), expressed as cost per mmol/mol reduction in glycated haemoglobin (HbA1c), was based on the mean difference in costs between the home and hospital groups, divided by mean differences in effectiveness (HbA1c). Uncertainty was considered in terms of the probability of cost-effectiveness. Results: At 24 months postintervention, the base-case analysis showed a difference in costs between home and hospital, in favour of home management (mean difference −£2, 217; 95% CI −£2825 to −£1, 609; p<0.001). Home care dominated, with an ICER of £7434 (saved) per mmol/mol reduction of HbA1c. The results of the scenario analysis also favoured home management. The greatest driver of cost differences was hospitalisation during the initiation period. Conclusions: Home management from diagnosis of children with T1D who are medically stable represents a less costly approach for the NHS in the UK, without impacting clinical effectiveness. Trial registration number: ISRCTN78114042 .